2018
DOI: 10.1177/2047487318786315
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain measured by speckle tracking identifies subclinical heart involvement in patients with systemic sclerosis

Abstract: Background Systemic sclerosis is characterised by progressive cutaneous and organ fibrosis. Among all organs, a subclinical heart involvement is difficult to detect through conventional imaging. Design We evaluated whether speckle tracking-derived global longitudinal strain could help detect early subclinical systolic dysfunction in systemic sclerosis patients without overt clinical involvement. Methods A case-control, single-centre study on 52 systemic sclerosis patients and 52 age and gender-matched controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
3
35
0
1
Order By: Relevance
“…However, few studies regarding three‐layer RV‐GLS have been reported thus far. Guerra et al found that the impairment of three‐layer GLS in patients with systemic sclerosis was homogeneous in the RV and heterogeneous in the LV (GLS‐epi most impaired), while Tadic et al demonstrated that a significant deterioration of RV‐GLS occurred in the endocardium and mid‐myocardium in chemo‐ and radio‐therapy‐naive patients with solid cancer. A reasonable explanation of these conflicting data, on one hand, could be the differences in cardiovascular risk factors and demographics of the study patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few studies regarding three‐layer RV‐GLS have been reported thus far. Guerra et al found that the impairment of three‐layer GLS in patients with systemic sclerosis was homogeneous in the RV and heterogeneous in the LV (GLS‐epi most impaired), while Tadic et al demonstrated that a significant deterioration of RV‐GLS occurred in the endocardium and mid‐myocardium in chemo‐ and radio‐therapy‐naive patients with solid cancer. A reasonable explanation of these conflicting data, on one hand, could be the differences in cardiovascular risk factors and demographics of the study patients.…”
Section: Discussionmentioning
confidence: 99%
“…The software automatically divided the wall into 3 layers: the inner third (endocardial layer), the middle third (mid‐myocardial layer), and the outer third (epicardial layer). Three‐layer GLS of the LV and RV (the ventricular septum was excluded from RV‐GLS calculations) were finally obtained (Figures and ) . Subjects with poor tracking quality for more than one of the 21 segments (18 LV segments and 3 RV segments) were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, a refinement in the evaluation of LV systolic function could be achieved by using global longitudinal strain, overcoming some limitations linked to LVEF measurements such as geometric assumptions and technical issues, such as apical foreshortening and difficulties in proper delineation of endocardial borders. 14,15 REACH-HF: cost-effectiveness of home-based cardiac rehabilitation in heart failure REACH-HF (Rehabilitation EnAblement in CHronic Heart Failure) is a home-based cardiac rehabilitation programme delivered over 12 weeks by a trained healthcare professional, co-developed with patients, caregivers and clinicians to include core components of comprehensive cardiac rehabilitation (i.e. education, psychological support and exercise training).…”
Section: Left Ventricular Function In Coronary Artery Diseasementioning
confidence: 99%
“…1,2 Although right heart catheterisation is required to establish the diagnosis and select appropriate treatment strategies in PH, cardiopulmonary and echo Doppler exercise testing along with strain imaging analysis may detect early signs of right heart pulmonary circulation unit dysfunction and provide additional prognostic information. [1][2][3][4] In this edition of the European Journal of Preventive Cardiology, Domenech-Ximenos et al compared 93 highly trained endurance athletes (53% men) with 72 healthy controls (58% men), who were younger and performed less than 3 hours moderate exercise per week. They underwent resting cardiovascular magnetic resonance (CMR) imaging to assess cardiac dimensions and function, as well as pulmonary artery dimensions and flow.…”
mentioning
confidence: 99%